National technology policies and international friction: Theory, evidence, and policy options - Karl-Heinz Paqué; Jürgen Stehn; Ernst-Jürgen Horn; Hans-Eckart Scharrer; Georg Koopmann (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
Economic theory and empirical evidence suggest that governments might usefully intervene in high-technology competition in two ways: First, they could act as a neutral agent that creates the necessary credibility, commitment and mutual trust among private companies so as to facilitate cooperation in high-risk, high-volume R&D. Second, if — in view of the externalities involved — an element of subsidization is to be added, this could be done in a nondiscriminatory fashion. A favourable tax treatment of R&D expenditures may be the most appropriate tool to achieve this task. In practice, governments do engage in targeted industrial and technology policies, whether justified on economic grounds or not. As a consequence, the string of trade conflicts in hightech industries that began in the 1980s is unlikely to end in the near future, unless substantial reforms are undertaken in some crucial areas of the international trade order. Above all, appropriate reform steps should be made with a view to the regulations on (i) subsidies, (ii) structural impediments, and (iii) dumping and anti-dumping. To mitigate the frictions that arise from a subsidization of domestic firms, a new set of rules should be established. The rules should provide that all plans to grant or to alter existing subsidies are to be notified to and approved by the WTO. Moreover, all subsidies should be ranked according to their potential distortional effects on competition and trade. For each category, quantitative limits that constrain the provision of subsidies to a certain fraction of the subsidy base should be set. To facilitate further liberalization steps, a country should be allowed to exceed these limits, if a national subsidy program offers an open access to firms located in third markets. Besides restrictive business practices of private firms, government regulations and technical standards are the most important structural impediments to trade. Existing GATT Articles already offer a multilateral route to conflict resolution in cases of structural impediments. However, this route has not been used by complainants up to now. The so-called "non-violation" clause of Article 23 GATT provides access to a multilateral dispute settlement even if the defending country has not explicitly violated GATT rules. This route should be tested and, if necessary, improved. To reduce the potential for a protectionist abuse of existing anti-dumping regulations, explicit reference to the state of competition in the relevant exporting and importing country markets should be made in anti-dumping investigations. To meet specific anti-trust concerns in hightech competition — notably with respect to network externalities, systems leverage, standardization, and innovation cartels — one might consider adopting the Draft International Antitrust Code (DIAC) that has recently been proposed by an international group of legal experts.
Keywords: 330